Nanomedicine‐Enabled/Augmented Cell Pyroptosis for Efficient Tumor Nanotherapy. Issue 35 (20th October 2022) - Zhang, Zheng; Zhou, Yajun; Zhao, Shuangshuang; Ding, Li; Chen, Baoding; Chen, Yu
Abstract: The terrible morbidity and mortality of malignant tumors urgently require innovative therapeutics, especially for apoptosis‐resistant tumors. Pyroptosis, a pro‐inflammatory form of programmed cell death (PCD), is featured with pore formation in plasma membrane, cell swelling with giant bubbles, and leakage of cytoplasmic pro‐inflammatory cytokines, which can remodel the tumor immune microenvironment by stimulating a "cold" tumor microenvironment to be an immunogenic "hot" tumor microenvironment, and consequently augment the therapeutic efficiency of malignant tumors. Benefiting from current advances in nanotechnology, nanomedicine is extensively applied to potentiate, enable, and augment pyroptosis for enhancing cancer‐therapeutic efficacy and specificity. This review provides a concentrated summary and discussion of the most recent progress achieved in this emerging field, highlighting the nanomedicine‐enabled/augmented specific pyroptosis strategy for favoring the construction of next‐generation nanomedicines to efficiently induce PCD. It is highly expected that the further clinical translation of nanomedicine can be accelerated by inducing pyroptotic cell death based on bioactive nanomedicines. Abstract : Nanomedicine‐induced pyroptosis for efficient tumor therapeutics is increasingly prominent at current stage. This review provides a comprehensive summary and deep discussion on the very‐recent progress achieved in this emerging field.